Influence of Web Based Cooperative Learning Strategy and Achiever Motivation on Student Study Outcome - Bambang Hariadi; Tutut Wurijanto (Institute of Advanced Engineering and Science, 2016)
The research aimed at examining the effect of instructional strategy (web-based STAD and text-based STAD) and achiever motivation toward student learning outcomes. The research implied quasi-experimental design with nonequivalen control group factorial version. The subjects were undergraduated students of Information Systems of academic year 2014/2015 at STIKOM Surabaya. Two groups were involved in the investigation with which amounts to 67 students, comprised of 34 students for the experimental class and 33 students for grade control. The collected data were statistically processed using analysis of variance techniques (ANOVA) two paths using a significance level of 0,05. The results of this research indicate that there is a difference in outcome study of Organization Behavior courses is significant between groups of students who studied with a web-based STAD type cooperative instrutional strategies and textual STAD type cooperative strategies. Based on the findings of this research, researchers suggest implementing STAD tipe cooperative of instructional strategy, with simultaneously (complementary) between the web-based and text-based in the form of blended learning.